Three new Anaulacomera species (Orthoptera: Tettigoniidae: Phaneropterinae) from the Iguaçu National Park and nearby areas, southern Brazil - Fianco, Marcos; Cadena-Castañeda, Oscar J.; Szinwelski, Neucir; Faria, Luiz R. R. (Zootaxa, 2021)
Three new species of Anaulacomera are described, Anaulacomera (Anaulacomera) mariellae sp. n. and Anaulacomera (Anallomes) arlindoi sp. n., belonging respectively to the Inermis and Lanceolata species group, and Anaulacomera angelinae sp. n., placed as incertae sedis. The individuals were collected at the Iguaçu National Park and adjacent small fragments of Atlantic Forest, in southwestern Paraná state, Brazil. The description was based on external morphology of males. We also present distribution maps for the species of the Inermis and the Lanceolata species groups.